Effects of HTLV-1 on leukocyte trafficking and migration in ACs compared to healthy individuals - Letafati, Arash; Bahavar, Atefeh; Norouzi, Mehdi; Rasouli, Aziz; Hedayatyaghoubi, Mojtaba; Molaverdi, Ghazale; Mozhgani, Sayed-Hamidreza; Siami, Zeinab (BMC research notes, 2024)
Human T-lymphotropic virus type 1 (HTLV-1) is a RNA virus belonging to Retroviridae family and is associated with the development of various diseases, including adult T-cell leukemia/lymphoma (ATLL) and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). Aside from HAM/TSP, HTLV-1 has been implicated in the development of several disorders that mimic auto-inflammation. T-cell migration is important topic in the context of HTLV-1 associated diseases progression. The primary objective of this case-control study was to assess the relationship between increased mRNA expression in virus migration following HTLV-1 infection. PBMCs from 20 asymptomatic patients and 20 healthy subjects were analyzed using real-time PCR to measure mRNA expression of LFA1, MLCK, RAC1, RAPL, ROCK1, VAV1 and CXCR4. Also, mRNA expression of Tax and HBZ were evaluated. Mean expression of Tax and HBZ in ACs (asymptomatic carriers) was 0.7218 and 0.6517 respectively. The results revealed a noteworthy upregulation of these genes involved in T-cell migration among ACs patients in comparison to healthy individuals. Considering the pivotal role of gene expression alterations associated with the progression into two major diseases (ATLL or HAM/TSP), analyzing the expression of these genes in the ACs group can offer probable potential diagnostic markers and aid in monitoring the condition of ACs.